Figure di sovranità, sovranità di figure. Su Un re in ascolto di Calvino - De Rosa, Nicola (Status Quaestionis, 2022)
Calvino prepares the different drafts of A King Listens in the context of the turbulent partnership with Luciano Berio, for a “musical action” to be presented at the Salzburger Festspiele in 1984. In the text, the king’s “ear-palace” tends to encompass everything that surrounds it and it functions as a synecdoche of the character himself. On the one hand, we witness the phono-sensorial experience which claims its value as knowledge, on the other, the drama of the sovereign and sovereignty, united by the morphological fact of an overload of figures and concepts. In Italy’s socio-political anxiety at the late 1970s, in which the con- ception of A King Listens falls, the text seems to violently problematize the modalities of knowledge of a more or less ‘sovereign’ subject.